Genetic Deletion of PGF2α-FP Receptor Exacerbates Brain Injury Following Experimental Intracerebral Hemorrhage - Mohan, Shekher; Koller, Emily J.; Fazal, Jawad A.; De Oliveria, Gabriela; Pawlowicz, Anna I.; Doré, Sylvain (Frontiers in Neuroscience, 2018)
Background: The release of inflammatory molecules such as prostaglandins (e.g. PGF2α) is associated with brain damage following an intracerebral hemorrhagic (ICH) stroke; however, the role of PGF2α and its cognate FP receptor in ICH remains unclear. Our study focused on investigating the FP receptor role as a target for novel neuroprotective drugs in a preclinical model of ICH. This study aimed to investigate the contribution of the PGF2α-FP axis in modulating functional recovery and anatomical outcomes following ICH. Results: Neurological deficit scores in FP-/- mice were significantly higher compared to WT mice 72h after ICH (6.1 ± 0.7 vs 3.1 ± 0.8; P < 0.01). Assessing motor skills, the total time mice stayed on the rotating rod was significantly less in FP-/-mice compared to WT mice 24h after ICH (27.0 ± 7.5 vs. 52.4 ± 11.2s). Using grip strength to quantify forepaw strength, results showed that the FP-/- mice had significantly less strength compared to WT mice 72h after ICH (96.4 ± 17.0 vs 129.6 ± 5.9g; P < 0.01). In addition to the behavioral outcomes, histopathological measurements were made. In Cresyl violet stained brain sections, the FP-/- mice showed a significantly larger lesion volume compared to the WT (15.0 ± 2.2 vs 3.2 ± 1.7mm3) mice. To estimate the presence of ferric iron in the peri-hematoma area, Perls’ staining was performed, which revealed that FP-/- mice had significantly greater staining than the WT mice (186.3 ± 34.4% vs 86.9 ± 13.0% total positive pixel counts, P < 0.05). Immunoreactivity experiments on brain sections from FP-/- and WT mice post-ICH were performed to monitor changes in microgliosis and astrogliosis using antibodies against Iba1 and GFAP respectively. These experiments showed that FP-/- mice had a trend towards greater astrogliosis than WT mice post-ICH. Conclusion: We showed that deletion of the PGF2α FP receptor exacerbates behavioral impairments, and lesion volumes following ICH compared to WT matched controls. Detailed mechanisms responsible for these novel results are actively being pursued.